ANALISIS PENGELOLAAN SAMPAH DI KECAMATAN PEDURUNGAN KOA SEMARANG - Bahana, Agra; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Waste management in a city aims to serve the waste of citizen trash to protect for healthy place environment and a good place for living. In the Pedurungan District, there are people who doesn’t care about waste management trash which is very important to reducing the trash. Illegal waste trash occur because the control from officer is weak. It makes the illegal trash feel free to waste. In this research the writer take the research of waste management processing in Pedurungan District Semarang City. In this research the writer used description method with interviewing the head of environmental services agency Semarang city and activies of waste management this research is purpose to describe and analysis how waste management serve cityzen in Pedurungan district Semarang city, depends on theory from Terry about 5 management function and describe what causes good waste management and factor made waste management ineffective. This research is to purpose that the waste management by environmental services agency Semarang city occurred a few problem on waste infrastructure and careless of citizen about waste management. Ineffective waste management made by illegal trash and less about activity of socialism how to reduce, reuse amd recycle the trash.